2021
DOI: 10.3390/healthcare9081034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rehabilitation Nutrition on a Post-Acute Severe COVID-19 Patient: A Case Report

Abstract: Coronavirus disease 2019 (COVID-19) may lead to post-acute physical function deterioration due to intensive-care-unit-acquired weakness-related sarcopenia and dyspnea. Limited reports have examined the effects of rehabilitation and nutritional therapy on patients with post-acute COVID-19. We present the case of a 67-year-old man, who was admitted for the treatment of post-acute severe COVID-19, who benefited from rehabilitation nutrition. When the patient’s condition stabilized, sarcopenia and malnutrition wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Most studies on the effect of exercise on functional capacity and pulmonary function after discharge from COVID-19 hospital are currently limited to observational studies [21]. However, the results of previous studies showed that exercise therapy in COVID-19 survivors had a significant effect on functional capacity, especially 6-minute walking distance [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and pulmonary function [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the effect of exercise on functional capacity and pulmonary function after discharge from COVID-19 hospital are currently limited to observational studies [21]. However, the results of previous studies showed that exercise therapy in COVID-19 survivors had a significant effect on functional capacity, especially 6-minute walking distance [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and pulmonary function [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to adopt specific strategies aimed at increasing muscle strength, such as working at adequate intensities and using blood flow restriction [140]. In this regard, previous studies have shown that a combination of aerobic training and RT increased muscle strength, functional capacity, and quality of life post COVID-19 infection [141][142][143].…”
Section: After: Resistance Training After Covid-19 Treatmentmentioning
confidence: 99%
“…40,52,56,59) Nutrient utilizationImprove nutrient utilization and contribute to better overall health and recovery. Exercise increases the body's demand for nutrients.…”
mentioning
confidence: 99%
“…Nutrients are more efficiently utilized to support recovery during rehabilitation (49,. 51,56) Patient compliance When patients see positive results from their rehabilitation efforts, they are more likely to stay motivated and adhere to their exercise and nutrition plans. The synergy between exercise and nutrition can lead to faster improvements, boosting patient confidence and compliance (21,.…”
mentioning
confidence: 99%
See 1 more Smart Citation